Aaron Ember and the Establishment of Egypto-Semitic Phonological and Lexical Comparison (Part II) - Takács, Gábor (Acta Orientalia Vilnensia, 2006)
Institute of Linguistics, Hungarian Academy of Science, Eötvös Loránd UniversityThe present paper represents the second half of the appraisal of Aaron Ember’s contribution to Egypto-Semitic etymology. The first part was introduced by a sketchy biography of Ember and an overview of his conception of Egypto-Semitic sound correspondences, which was followed by the analysis and evaluation of those Egypto-Semitic etymologies proposed by Ember that have to be either abandoned or complemented in the testimony of current progress in Afro-Asiatic linguistic comparison. For technical reasons, this list was restricted to the Egyptian roots with 3- to p- in Anlaut. This is why the following etymological material encompasses Egyptian roots with m- to d-.